Suitable Diversions: Women, Gentility and Entertainment in an Imperial Outpost - Errington, Elizabeth (Ontario History, 2010)
What Upper Canadians in the first half of the nineteenth century thought of as entertainment was fundamentally shaped by their class and their gender. While for many, the local tavern was a natural site to socialize it held little appeal for the cultured gentlewoman. Whether living on a backwoods farm or presiding over a big house in town, the wives and daughters of prominent Upper Canadians and gentlemen farmers consciously embraced the genteel leisure of the domestic circle. They sought companionship from others of their rank and sensibilities; and they enjoyed those diversions that both reflected their personal tastes and interests, but also symbolized their essential identity—gentlewomen of the empire.